Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.47836/pjst.30.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Compression and Flexural Behavior of ECC Containing PVA Fiber

Abstract: Research on Engineered Cementitious Composites (ECC) is overwhelming owing to its wide structural applications that can serve multi-functional purposes in civil and nvironmental infrastructures. Compared to other high-performance fiber reinforced concrete, ECC yields superior tensile ductility and multiple cracking behaviors when subjected to tensile loadings even with low to moderate volume of fibers. This paper presents the flexural properties of ECC made of cement, an industrial by-product, such as ground g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, G80F2.5 achieves the lowest compressive strength 37.56 MPa, and the value is lower than the control (G0F2.5), which is 43.52 MPa. The data found that a higher content of GGBS tends to give a lower value in compressive strength [13] specifically after 70% replacement of GGBS. In line with previous studies from [8] that the compressive strength is at highest at 70% of the GGBS replacing cement.…”
Section: Compressive Strengthmentioning
confidence: 92%
“…On the other hand, G80F2.5 achieves the lowest compressive strength 37.56 MPa, and the value is lower than the control (G0F2.5), which is 43.52 MPa. The data found that a higher content of GGBS tends to give a lower value in compressive strength [13] specifically after 70% replacement of GGBS. In line with previous studies from [8] that the compressive strength is at highest at 70% of the GGBS replacing cement.…”
Section: Compressive Strengthmentioning
confidence: 92%